New applications of the nanopositioning and nanomeasuring machine by using advanced tactile and non-tactile probes - Manske, Eberhard; Hausotte, Tino; Mastylo, Rostyslav; Machleidt, Torsten; Franke, Karl-Heinz; Jäger, Gerd (Institute of Physics: Hybrid Open Access, 2007)
With the nanopositioning and nanomeasuring machine (NPM-Machine) developed at the Technische Universitat Ilmenau, subnanometre resolution and nanometre uncertainty in a measuring volume of 25 x 25 x 5 mm(3) have been demonstrated in the last few years. This machine allows the most various measuring problems to be solved. In practice, however, there are too many different requirements for sensing surfaces or for detecting structures. So, this paper deals with the development and also the improvement of several optical and tactile probes for application in the NPM-Machine. A focus probe with a spot size of approximately 0.5 mu m, a working distance of 1.5 mm and a resolution of less than 1 nm was developed and adopted in the NPM-Machine. In the next step, the working distance was improved to exploit the full vertical range of the NPM-Machine of 5 mm. To realize tactile sensing, an atomic force probe and tactile stylus probe were developed on the basis of the focus probe. These probing systems can acquire measuring data only by scanning the surface sequentially and point-by-point. To increase data acquisition, we realized a sensor based on a white-light interference microscope and parallel sampling of 1600 x 1200 data points. First results of fringe evaluation with laser interferometer reference are presented.
Keywords: nanopositioning and nanomeasuring machine; focus probe; tactile stylus probe; white-light interferometer